Gadofosveset-enhanced magnetic resonance imaging as a problem-solving tool for diagnosing colorectal liver metastases: a case report - Cheung, Helen (Quant Imaging Med Surg, 2018)
Due to significant improvements in morbidity and mortality, surgery with curative intent is now the standard of care for patients with colorectal liver metastases who are surgical candidates. As a result, highly accurate preoperative per-lesion diagnosis is crucial. However, in some instances, this remains limited with standard techniques, including magnetic resonance imaging (MRI) with conventional contrast agents. Delayed retention of contrast of fibrotic liver metastases on MRI with extracellular contrast agents may mimic the late retention of contrast in hemangiomas and represent a diagnostic pitfall that limits diagnosis. Early preliminary work suggests that this imaging pitfall may not be seen on MRI with intravascular contrast agents (e.g., gadofosveset). This case report describes a surgical patient with colorectal liver metastases where gadofosveset-enhanced liver MRI was helpful in determining patient management.